332 Improvement in symptoms of atopic dermatitis (AD) and AD-related quality of life with dupilumab treatment in adults: 24-week results of the DUPISTAD study. (25th January 2023) - Merola, Joseph F; Chiou, Albert S; During, Emmanuel; Costanzo, Antonio; Foley, Peter; Ardeleanu, Marius; Wu, Jiangming; Ozturk, Zafer E
Abstract: Atopic dermatitis (AD) is a chronic disease characterized by sleep disturbance, associated with night-time itching and scratching, along with skin pain, resulting in daytime drowsiness, diminished daytime productivity and overall reduced quality of life (QoL) in patients with AD. To report the effect of up to 24 weeks of dupilumab treatment on the QoL of adult patients with moderate-to-severe AD, using data from the DUPISTAD (NCT04033367) study. Phase 4, a randomized DUPISTAD study, comprised two 12-week periods: an initial placebo-controlled double-blind period, and a subsequent 12-week open-label extension (OLE) period. Adult patients with moderate-to-severe AD (Eczema Area and Severity Index score ≥12, Peak Pruritus Numeric Rating Scale [NRS] score ≥3, Sleep Disturbance NRS average score ≥5), showing an inadequate response to topical treatments, were randomized 2 : 1 to dupilumab 300 mg every 2 weeks (q2w) for both the double-blind and OLE periods or placebo for the initial double-blind period, followed by dupilumab 300 mg q2w for the OLE period. The use of concomitant topical corticosteroids was permitted during the entire course of the study. Endpoints, including Patient-Oriented Eczema Measure (POEM; scored 0–28, with higher values indicating a worse outcome), Dermatology Life Quality Index (DLQI; scored 0–30, with higher values indicating a poorer QoL), Skin Pain and Sensitivity NRS (scored 0–10, where 0 = no pain/normal sensitivity and 10 = worst possible pain/extremely sensitive) were assessed from baseline to week 24. The enrolled patients also completed a Work Productivity and Activity Impairment Questionnaire (WPAI-AD), including an NRS rating of the AD-Affected Ability to do Regular Daily Activities other than a Job (scored 0–10, where 0='no effect' and 10='prevented me from doing my daily activities'). Formal statistical comparisons were not performed on the data resulting from the OLE period. The DUPISTAD study enrolled a total of 188 patients: 127 patients received dupilumab throughout (dupilumab–dupilumab group), and 61 patients received a placebo and then switched to dupilumab (placebo–dupilumab group). Baseline demographics and disease characteristics were well balanced. Improvement from baseline in AD-related patient-reported QoL indicators and AD symptoms was observed at week 24 in both groups, as illustrated by the mean change from baseline in POEM total scores (−14.6 in the dupilumab–dupilumab group and −15.9 in the placebo–dupilumab group), DLQI scores (−12.6 in the dupilumab–dupilumab group and −13.4 in the placebo–dupilumab group), Skin Pain NRS scores (−4.7 in the dupilumab–dupilumab group and −5.0 in the placebo–dupilumab group), Skin Sensitivity NRS scores (−4.6 in the dupilumab–dupilumab group and −5.0 in the placebo–dupilumab group), and the WPAI-AD NRS of Ability to do Regular Daily Activities scores (−4.2 in the dupilumab–dupilumab group and −3.8 in the placebo–dupilumab group). The placebo–dupilumab group experienced most of this improvement during the OLE period, as illustrated by the mean change from week 12 to week 24 in POEM total score (−11.5), DLQI score (−5.5), Skin Pain NRS score (−3.0), Skin Sensitivity NRS score (−3.0) and the WPAI-AD NRS of Ability to do Regular Daily Activities score (−2.0). The safety profile of dupilumab was consistent with the known safety profile. Dupilumab provided sustained improvements through 24 weeks in AD-related patient-reported measures of QoL and AD symptoms in adults with moderate-to-severe AD. Patients who were switched from placebo to dupilumab at week 12 showed rapid improvement in these parameters after the switch, eventually matching the improvement achieved by patients who received dupilumab from baseline through week 24.